Earlier physical therapy input is associated with a reduced length of hospital stay and reduced care needs on discharge in frail older inpatients: an observational study - Romero-Ortuno, Roman (My University, 2019)
Background and purpose: Pressures on hospital bed occupancy in the English National Health Service have focused attention on enhanced service delivery models and methods by which physical therapists might contribute to effective cost savings, while retaining a patient-centered approach. Earlier access to physical therapy may lead to better outcomes in frail older inpatients, but this has not been well studied in acute National Health Service hospitals. Our aim was to retrospectively study the associations between early physical therapy input and length of hospital stay (LOS), functional outcomes, and care needs on discharge. Methods: This was a retrospective observational study in a large tertiary university National Health Service hospital in the United Kingdom. We analyzed all admission episodes of people admitted to the department of medicine for the elderly wards for more than 3 months in 2016. Patients were categorized into 2 groups: those examined by a physical therapist within 24 hours of admission and those examined after 24 hours of admission.The outcome variables were as follows: LOS (days), functional measures on discharge (Elderly Mobility Scale and walking speed over 6 m), and the requirement of formal care on discharge. Characterization variables on admission were age, gender, existence of a formal care package, preadmission abode, the Clinical Frailty Scale, Charlson Comorbidity Index, the Emergency Department Modified Early Warning Score, C-reactive protein level on admission, and the 4-item version of the Abbreviated Mental Test.The association between the delay to physical therapy input and LOS before discharge home was evaluated using a Cox proportional hazards regression model. Results and discussion: There were 1022 hospital episodes during the study period. We excluded 19 who were discharged without being examined by a physical therapist. Of the remaining 1003, 584 (58.2%) were examined within 24 hours of admission (early assessment) and 419 (41.8%) after 24 hours of admission (late assessment).The median (interquartile range) LOS of the early assessment group was 6.7 (3.1-13.7) versus 10.0 (4.2-20.1) days in the late assessment group, P < .001. The early assessment group was less likely to require formal care on discharge: n = 110 (20.3%) versus n = 105 (27.0%), P = .016. No other statistically significant differences were seen between the 2 groups.In the unadjusted Cox proportional hazards model, the hazard ratio for early assessment compared with late assessment was 1.29 (95% confidence interval: 1.12-1.48, P < .001). Early assessment was associated with a 29% higher probability of discharge to usual residence within the first 21 days after admission than the late assessment. Adjustment for possible confounding variables increased the hazard ratio: 1.34 (1.16-1.55), P < .001. Conclusions: Early physical therapy input was associated with a shorter LOS and lower odds of needing care on discharge. This may be due to the beneficial effect of early physical therapy in preventing hospital-related deconditioning in frail older adults. However, causality cannot be inferred and further research is needed to investigate causal mechanisms.
Keywords: frail older adults; hospital bed occupancy; English National Health Service; Physical therapy; Outcome assessments; England; Older adults; Acute care; Ageing